Code-Mixing and Code Switchingin The Process of Learning - Diyah Atiek Mustikawati (Register Journal, 2016)
This study aimed to describe a form of code switching and code mixing specific form found in the teaching and learning activities in the classroom as well as determining factors influencing events stand out that form of code switching and code mixing in question.Form of this research is descriptive qualitative case study which took place in Al Mawaddah Boarding School Ponorogo. Based on the analysis and discussion that has been stated in the previous chapter that the form of code mixing and code switching learning activities in Al Mawaddah Boarding School is in between the use of either language Java language, Arabic, English and Indonesian, on the use of insertion of words, phrases, idioms, use of nouns, adjectives, clauses, and sentences. Code mixing deciding factor in the learning process include: Identification of the role, the desire to explain and interpret, sourced from the original language and its variations, is sourced from a foreign language. While deciding factor in the learning process of code, includes: speakers (O1), partners speakers (O2), the presence of a third person (O3), the topic of conversation, evoke a sense of humour, and just prestige. The significance of this study is to allow readers to see the use of language in a multilingual society, especially in AL Mawaddah boarding school about the rules and characteristics variation in the language of teaching and learning activities in the classroom. Furthermore, the results of this research will provide input to the ustadz / ustadzah and students in developing oral communication skills and the effectiveness of teaching and learning strategies in boarding schools.